Detection of crayfish plague spores in large freshwater systems. Issue 2 (19th February 2014) - Strand, David A.; Jussila, Japo; Johnsen, Stein I.; Viljamaa‐Dirks, Satu; Edsman, Lennart; Wiik‐Nielsen, Jannicke; Viljugrein, Hildegunn; Engdahl, Frederik; Vrålstad, Trude; Morgan, Eric
Summary Indigenous European freshwater crayfish (ICS) are threatened due to invasive North American freshwater crayfish that are natural carriers of Aphanomyces astaci which causes crayfish plague. Infectious A. astaci zoospores are released from carrier crayfish, but little is known about the spore abundance in water systems that either host non‐indigenous crayfish species (NICS) or experience crayfish plague outbreaks. We tested two large‐scale filtering approaches to generate new insight about the abundance and dynamics of A. astaci spores in natural freshwater systems. Depth filtration (DF) and dead‐end ultrafiltration (DEUF) followed by A. astaci‐specific quantitative real‐time PCR was used to monitor A. astaci spores in large Nordic lakes hosting A. astaci‐positive Pacifastacus leniusculus, the dominating NICS in Northern Europe. Crayfish and water were sampled together to compare the A. astaci pathogen load in tissues, A. astaci prevalence in the population and the corresponding spore density in water. Samples were also obtained from a river where indigenous noble crayfish suffered from acute crayfish plague. The sensitivity of the filtering techniques was evaluated using simulation of random events. We detected A. astaci spores in lakes hosting NICS with both filtering methods but predominantly at concentrations below c. 1 spore L−1. We found a significant positive association between A. astaci spore density in water, the A. astaci prevalence in the corresponding NICS population and the tissue pathogen load. Water from the river with the ongoing crayfish plague outbreak contained overall c. 43 times more spores L−1 than water hosting NICS. Both filtering techniques proved suitable and equally sensitive, but simulations suggest that an optimization of the spore recovery could yield a 10‐fold increase in the DEUF‐method sensitivity. Synthesis and application. Our study demonstrates a low amount of pathogen spores are present in aquatic environments with non‐indigenous crayfish species, emphasizing the need for large‐volume filtering techniques for successful detection. The approach can be used for risk assessments and to improve conservation and management strategies of crayfish in Europe. Applications of this method include targeted disease surveillance, habitat evaluation prior to crayfish re‐stockings and water monitoring that can minimize disease transmission and spread, for example in crayfish farms and prior to fish movements for stocking purposes.